ANALISIS PEMBIAYAAN DALAM PENGADAAN POMPA DEWATERING PADA PT. HARMONI PANCA UTAMA DI BONTANG - Wibisono, Ovan Sandi (EKONOMIA, 2019)
Analysis of financing in the procurement of Dewatering Pumps at PT. Harmoni Panca Utama in Bontang under the guidance of L.C.A Robin Jonathan and Sunarto. This study generally aims to determine the effect of financing in the procurement of Dewatering Pumps at PT. Harmony of the Main Panca in Bontang. Specifically this research aims to find out that renting a Dewatering Pump is more profitable for PT. Harmoni Panca Utama in Bontang. To find out and analyze information on operational costs of the contract / lease influence in decision making by the PT. Harmoni Panca Utama in Bontang in buying Dewatering Pumps. Data analysis used by the writer in this final project report is quantitative descriptive method. The method used by the author calculates with each of them based on the data that has been obtained. Steps - steps of calculation in making a decision to buy or lease with the calculation of PV, FV and NPV in buying and leasing a Dewatering Pump at PT Harmoni Panca Utama. And compare the calculation of the cost of buying or renting a Dewatering Pump for PT Harmoni Panca Utama. The results of the study revealed that the value of investment and renting had a very significant difference in procuring MF 385 dewatering pumps at PT. Harmoni Panca Utama in Bontang. The value of PV investment per unit is IDR 2,855,000,000 and the value of PV leasing per unit is IDR 6,219,630,709 while the value of FV investment is less than the FV value of lease which is IDR 3,305,019,375 for FV Investment and IDR 7,200,000,000 for FV leasing, as well as the investment NPV value is less than the NPV value of the lease, namely Rp. 450,019,375 for the NPV value of investment and Rp. 980,369,219 for the lease NPV value. Then in accordance with the results of the above calculations, the hypothesis is rejected, which means rent is more detrimental in the procurement of Dewatering Pumps at PT. Harmoni Panca Utama in Bontang.